2016
DOI: 10.1038/srep28715
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16 Deficiency Attenuates Renal Injury and Fibrosis in Salt-Sensitive Hypertension

Abstract: Inflammation plays an important role in the pathogenesis of hypertensive kidney disease. However, the molecular mechanisms underlying the induction of inflammation are not completely understood. We have found that CXCL16 is induced in the kidney in deoxycorticosterone acetate (DOCA)-salt hypertension. Here we examined whether CXCL16 is involved in DOCA-salt-induced renal inflammation and fibrosis. Wild-type and CXCL16 knockout mice were subjected to uninephrectomy and DOCA-salt treatment for 3 weeks. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
(87 reference statements)
0
30
0
Order By: Relevance
“…Renal expression of CXCL16 is upregulated in Ang II-induced and DOCA-salt hypertension (67, 68). In both hypertensive models, CXCL16-deficient mice have similar blood pressure to wild-type controls.…”
Section: Chemokinesmentioning
confidence: 99%
“…Renal expression of CXCL16 is upregulated in Ang II-induced and DOCA-salt hypertension (67, 68). In both hypertensive models, CXCL16-deficient mice have similar blood pressure to wild-type controls.…”
Section: Chemokinesmentioning
confidence: 99%
“…These results suggest that CXCR6 plays a critical role in the development of DOCA/salt-induced hypertensive nephropathy by mediating the recruitment of myeloid fibroblasts and inflammatory cells into the kidney. www.nature.com/scientificreports www.nature.com/scientificreports/ Recently, we have demonstrated that CXCL16 recruits myeloid fibroblasts, macrophages and T lymphocytes into the kidney resulting in kidney injury and fibrosis in a DOCA/salt model of hypertension 9 . CXCL16 regulates circulating cell trafficking via interaction with its receptor CXCR6 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory and immune cells are recruited into the kidney by chemokines through interacting with their respective receptors 6,26,32 . Recently, we have demonstrated that genetic deletion of CXCL16 suppresses inflammatory and immune cell infiltration into the kidney following DOCA/salt-induced hypertension 9 . In the present study, we report that the infiltration of macrophage and T lymphocytes into the kidney is dramatically reduced in CXCR6 deficient mice treated with DOCA/salt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic deletion of CXCL16 protects the kidney from renal dysfunction, inhibits renal fibrosis, reduces proteinuria, suppresses bone marrow-derived fibroblast accumulation, myofibroblast formation, macrophage and T cell infiltration and pro-inflammatory cytokine expression with no effect on Ang II-induced hypertension 30 . More recently, we have shown that CXCL16 plays a crucial role in the development of kidney fibrosis induced by DOCA/salt and renal artery stenosis 31, 32 .…”
Section: Introductionmentioning
confidence: 99%